Columnar shifts as symmetry-breaking degrees of freedom in molecular perovskites. Issue 46 (14th November 2016) - Boström, Hanna L. B.; Hill, Joshua A.; Goodwin, Andrew L.
Abstract : Columnar shifts are degrees of freedom in molecular perovskites of relevance to phase transitions, improper ferroelectricity, and negative thermal expansion. Abstract : We introduce columnar shifts—collective rigid-body translations—as a structural degree of freedom relevant to the phase behaviour of molecular perovskites ABX3 (X = molecular anion). Like the well-known octahedral tilts of conventional perovskites, shifts also preserve the octahedral coordination geometry of the B-site cation in molecular perovskites, and so are predisposed to influencing the low-energy dynamics and displacive phase transitions of these topical systems. We present a qualitative overview of the interplay between shift activation and crystal symmetry breaking, and introduce a generalised terminology to allow characterisation of simple shift distortions, drawing analogy to the "Glazer notation" for octahedral tilts. We apply our approach to the interpretation of a representative selection of azide and formate perovskite structures, and discuss the implications for functional exploitation of shift degrees of freedom in negative thermal expansion materials and hybrid ferroelectrics.